The increase of physiological optimum of nitrogen for plants by inoculation and use of plant growth regulators - Volkogon, V.V. (Сільськогосподарська мікробіологія, 2008)
As was established in greenhouse experiments ssusing isotope dilution method and confirmed by field investigations, conducted on grey-forest and sod-podzol soils, the inoculation and (or) treatment of cereal grasses with growth stimulators enhances plants’ physiological optimum in nitrogen and thus improves ecological state of agrocenoses by increasing fertilizers assimilation rate and their involvement into the constructive metabolism. At this, typically high doses of mineral nitrogen combined with plants growth stimulators become ecologically acceptable.